PENINGKATAN HASIL BELAJAR PENJUMLAHAN PECAHAN BERPENYEBUT BERBEDA DENGAN PENDEKATAN KONSTRUKTIVISME DI SEKOLAH DASAR - Febriyanti, Riska (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research backed by the learning still teacher center. Purpose of the research are described the planning implementation and learn outcomes in the summination of different denominator fraction learning with used constructivism approach. Subject in the research is teacher and student in forth grade at SDN 03 Bandar Buat. The research was conducted use qualitative and quantitative approaches. The results showed  increased of student learning outcomes from 74 increase to 80, with excellent qualifications. Kata Kunci : hasil belajar; penjumlahan pecahan; berpenyebut berbeda; konstruktivisme